Is a diet low in greenhouse gas emissions a nutritious diet? - Analyses of self-selected diets in the LifeGene study - Katarina Bälter; Camilla Sjörs; Arvid Sjölander; Christopher Gardner; Fredrik Hedenus; Annika Tillander (BMC, 2017)
Abstract Background Climate change is an urgent global issue and the food sector is a major contributor to greenhouse gas emissions (GHGE). Here we study if a diet low in GHGE could be a nutritious diet compared to the Nordic Nutrition Recommendations (NNR). Methods The environmental impact of foods from Life Cycle Assessment (LCA) data was linked to a food frequency questionnaire (FFQ) filled out by 5,364 participants in the Swedish LifeGene study. Thereafter, we calculated the daily emission of CO2 equivalents (CO2e) as well as the intake of selected nutrients associated with vegetables, fruits, meat and dairy products. The CO2e was divided into quartiles were quartile 1 corresponds to a diet generating the lowest CO2e, and quartile 4 corresponds to a diet with the highest CO2e. Results The overall diet-related emission was 4.7 kg CO2e/day and person, corresponding to 1.7 ton CO2e/year. In general, there were only small differences in nutrient intake between groups of varying levels of CO2e, regardless if the intake was analyzed as absolute intake, energy percent or as nutrient density. Moreover, adherence to NNR was high for the group with the lowest CO2e, except for saturated fat where the intake was higher than recommended for all CO2e groups. On the other hand, only the group with the lowest CO2e fulfilled recommended intake of fiber. However, none of the CO2e groups reached the recommended intake of folate and vitamin D. Conclusions Here we show that a self-selected diet low in CO2e provides comparable intake of nutrients as a diet high in in CO2e.